Sensory denervation in motor neuron disease - (:unkn) unknown (Nova Science Publishers, Inc., 2020)
Identification of amyotrophic lateral sclerosis (ALS) requires demonstration of denervation in motor fibres while sensory fibres are frequently expected to be spared. However, different aspects of sensory involvement in this disease have been extensively reported by many groups for the last three decades. Unfortunately, both the studies with conflicting results and the catastrophic clinical picture due to motor neuron degeneration placed sensory involvement in a relatively neglected position. Today, studies with a new perspective on sensory network in motor neuron diseases are conducted to understand the true extent and patophysiology of ALS and suggest new potential biomarkers to diagnose this tragic disease. © 2020 Nova Science Publishers, Inc.